A decision-support methodology for the energy design of sustainable buildings in the early stages. Issue 1 (1st January 2019) - Velázquez, Ernesto; Bruneau, Denis; Aketouane, Zakaria; Nadeau, Jean-Pierre
Abstract: A holistic approach integrating all aspects of building design directly affected by its energy performance is necessary for supporting decision-making throughout the design process. In this work, a decision-support methodology for the energy design of buildings is proposed, considering the three dimensions of the concept of sustainability, and adapted to the level of information detail available in the early design stages. The 4 modules composing this methodology are (i) a set of 36 key design variables defining the building design, (ii) a set of 16 indicators covering environmental, economic and user comfort aspects of building performance affected by energy-related design decisions, (iii) a calculation method for the performance indicators composed of 7 simulation models, and (iv) a knowledge base of building elements, energy sources and meteorological data. The methodology is primarily aimed to assist architects and engineers who participate in the design of office buildings in a French context.